A. CERVILLA GARCÍA - Estructuras vistas, ocultas e ilusorias - Flores Soto, José Antonio (ZARCH, 2017)
Alejandro Cervilla García Estructuras vistas, ocultas e ilusorias Diseño, Buenos Aires, 2016. 256 págs; 18’20 €